2023
DOI: 10.3389/fbioe.2023.1140527
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and inter-subject variability of femoral growth plate stresses in typically developing children and children with cerebral palsy

Abstract: Little is known about the influence of mechanical loading on growth plate stresses and femoral growth. A multi-scale workflow based on musculoskeletal simulations and mechanobiological finite element (FE) analysis can be used to estimate growth plate loading and femoral growth trends. Personalizing the model in this workflow is time-consuming and therefore previous studies included small sample sizes (N < 4) or generic finite element models. The aim of this study was to develop a semi-automated toolbox … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…In the future, altering joint loads with personalized muscle coordination retraining might help to treat or prevent clinical symptoms in a non-invasive way. For example, the direction of the hip JCF has been shown to determine typical and pathological growth plate stresses and bone growth 9 , 54 . Normalizing the direction of the hip JCF with personalized muscle coordination retraining at an early stage might, therefore, help to prevent the development of torsional femoral deformities.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, altering joint loads with personalized muscle coordination retraining might help to treat or prevent clinical symptoms in a non-invasive way. For example, the direction of the hip JCF has been shown to determine typical and pathological growth plate stresses and bone growth 9 , 54 . Normalizing the direction of the hip JCF with personalized muscle coordination retraining at an early stage might, therefore, help to prevent the development of torsional femoral deformities.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent simulation study, Kainz et al [ 18 ] showed that the orientation of the HJCF in the sagittal plane can differentiate between children with CP who are likely to have typical and pathological femoral growth. Asymmetric HJCF can alter growth plate loading [ 19 ] and therefore lead to asymmetric development of bones in length and shape resulting in altered biomechanics. Previous studies showed that not only the subject-specific gait pattern but also the femoral geometry has a big impact on the estimation of the HJCF [ 16 , 20 22 ].…”
Section: Introductionmentioning
confidence: 99%